PENERAPAN METODE PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) UNTUK MENINGKATKAN PARTISIPASI DAN KERJA TIM (TEAM WORK) MAHASISWA PENDIDIKAN EKONOMI PADA MATA KULIAH EKONOMI PENDIDIKAN - Sitaman Said; Fitriani Fitriani; Mukhlis Mukhlis (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
This study aims to analyze the application of the Project Based Learning (PjBL) method in improving student participation and teamwork in the Economics Education study program at Nggusuwaru University in the Economics Education course. The study used a qualitative descriptive approach with a classroom action research (CAR) design implemented in two cycles. Data were collected through observation, interviews, reflection, and analysis of student project documents. The results showed that the systematic application of PjBL through the stages of determining fundamental questions, project planning, scheduling, collaboration management, product/recommendation development, and presentation had a significant impact on increasing student participation, active involvement, communication, and the ability to work together in teams. In the first cycle, student participation increased from the moderate category to good, and in the second cycle it increased to excellent. Similarly, teamwork experienced improvements in the aspects of task division, communication, conflict resolution, and group responsibility. The application of PjBL allows students to connect educational economics theory with real phenomena, develop critical thinking skills, and increase their sense of ownership of the learning process. This study confirms that PjBL is an effective pedagogical approach for developing soft skills and collaborative competencies of economics students. The implications of the research point to the need for curriculum modification, lecturer training, and the provision of supporting facilities so that project-based learning can be implemented sustainably in higher education.